Burns, Baby, Burns: jazz history as a contested cultural site - Stanbridge, Alan (Jazz Research Journal, 2004)
The controversial critical reception of Ken Burns’s PBS documentary Jazz (2001) served to highlight the extent to which jazz history remains a highly contested cultural site. The debate over Burns’s documentary played out in both the popular press and academic journals throughout late-2000 and 2001,1 and still offers a lively discussion topic in jazz circles. Although the title of my paper might appear to hold out the promise of a review of the links between Ken Burns’s work and 1970s disco music, these are avenues that I will leave unexplored. Rather, my concern is to examine the manner in which the controversy represented another ongoing skirmish on the discursive battlefield that is jazz history, suggesting the need for a considerably broader conceptualization of jazz – and jazz history – than that offered in Burns’s documentary.